Pemberdayaan Kader Kesehatan dalam Pencegahan dan Deteksi Dini Penyakit Ginjal di Kecamatan Tugu - Restuning Prihati, Dyah; Prasetyorini, Heny (Jurnal Pengabdian Bidang Kesehatan, 2025)
Early detection of kidney disease is measured in terms of positive aspects where patient care can be given at the right time, improving a person's quality of life, and intervention can be given at an early stage of kidney disease, thus saving medical costs. The purpose of this activity is to provide education to health cadres to understand early detection and prevention of kidney disease so that the community understands and has knowledge about kidney disease. The stages of the implementation method, namely the socialization and training methods, aim to provide education to the community about the prevention and early detection of kidney disease. Health cadres who participated in PKM before being given education on prevention and early detection of kidney disease were 70% with a low level of knowledge, after being given education on prevention and early detection of kidney disease, it increased to 90% with a good level of knowledge. This proves that health education can be understood by health cadres. It is important to provide education on how to increase family support to help prevent and detect kidney disease early.